PENGARUH STRUKTUR MODAL, KEBIJAKAN DIVIDEN DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Tantono, Willy; Candradewi, Made Reina (E-Jurnal Manajemen; Vol 8 No 8 (2019)DO - 10.24843/EJMUNUD.2019.v08.i08.p06, 2019)
This study was conducted to examinate the effect of capital structure, dividend policy and liquidity on profitability of bank that listed on Indonesia Stock Exchange period of 2015 to 2017. This study was associative research. The population of this study were 39 companies and observed during 2015 to 2017. The sampling technique used in this study was saturated samples. Based on these techniques, 39 companies obtained as samples. This study used the secondary data from IDX. The data collection methods used in this study was non participant observation method. The researcher used multiple linear regression as the analytical technique. SPSS 20 was used to help analyze. The result of analysis can be conclude Capital Structure had significant negative effect on profitability, Dividend policy had significant positive effect on profitability and Liquidity had positive significant effect on profitability. Keywords : profitability, capital structure, dividend policy, liquidity